Otherworldly and eschatological priesthood in the Dead Sea scrolls - Angel, Joseph L. (Studies on the texts of the desert of Judah, 2010)
Pt. 1. Otherworldly priesthood in the Dead Sea scrolls. Otherworldly priesthood in non-sectarian writings -- Otherworldly priesthood in the songs of the sabbath sacrifice: imago templi and liturgical time at Qumran -- Otherworldly priesthood in sectarian writings -- Pt. 2. Eschatological priesthood in the Dead Sea scrolls. The image of eschatological priesthood in the Dead Sea scrolls -- The historical roots of the eschatological priesthood -- The traditional roots of the eschatological priesthood -- Summary and conclusions